Outcome of Anterior Cervical Decompression and Fusion for Cervical Spondylotic Myelopathy - Rahman, Md Salim Ur; Mohammad Russel, -; Karim, Mohd Rezaul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Anterior cervical discectomy and fusion (ACDF) is a common procedure for a patient with progressive spinal cord compression and severe neurological deterioration causing major disability. Surgery in anterior approach involves removal of osteophyte and disc materials for decompression of spinal cord with addition to the interposition of autogenous tricortical bone graft and stabilization by plate and screw. Objectives: To assess the clinical outcome, complications of anterior cervical decompression and fusion for cervical spondylotic myelopathy. Materials and Methods: This prospective interventional study was carried out in the Department of Orthopaedic Surgery, Combined Military Hospital, Dhaka from January 2015 to May 2017. Total of 24 cases of cervical spondylotic myelopathy was enrolled as a study sample. All were treated by an anterior cervical discectomy, fusion and stabilization by plate and screw. All patients were clinically and radiographically evaluated before and after surgery. Results: In the majority (62.5%) patients, the level of involvement was in C5/C6 and 92.8% had a satisfactory outcome. In 4.1% of cases, early complication like superficial wound infection was noted. Late complications were persistence of pain, numbness present in 7.2% cases. The fusion rate was 100% in this series. Conclusion: Anterior cervical decompression and fusion for cervical spondylotic myelopathy is a safe and effective procedure. It is associated with the highest fusion, least complications and relatively lower cost. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 127-129